Yesterday is history - Jackson, Kosoko (Sourcebooks Fire, 2021)
After a liver transplant, Andre suddenly becomes a time traveler, but is his soulmate Michael, who lives in 1969, or Blake, his donor's brother, who is training him in 2021?